Network analysis of the relationships between depressive symptoms and social participation activities among Chinese older adults and its implications for nursing - Yebo Yu; Hewei Min; Wei Pan; Ping Chen; Xuxi Zhang; Xinying Sun (Elsevier, 2024)
Objective: Network analysis was used to explore the complex inter-relationships between social participation activities and depressive symptoms among the Chinese older population, and the differences in network structures among different genders, age groups, and urban-rural residency would be compared. Methods: Based on the 2018 wave of the Chinese Longitudinal Healthy Longevity Survey (CLHLS), 12,043 people aged 65 to 105 were included. The 10-item Center for Epidemiologic Studies Depression (CES-D) Scale was used to assess depressive symptoms and 10 types of social participation activities were collected, including housework, tai-chi, square dancing, visiting and interacting with friends, garden work, reading newspapers or books, raising domestic animals, playing cards or mahjong, watching TV or listening to radio, and organized social activities. R 4.2.1 software was used to estimate the network model and calculate strength and bridge strength. Results: 21.60% (2,601/12,043) of the participants had depressive symptoms. The total social participation score was negatively associated with depressive symptoms after adjusting for sociodemographic factors. The network of social participation and depressive symptoms showed that "D9 (Inability to get going)" and "S9 (Watching TV and/or listening to the radio)" had the highest strength within depressive symptoms and social participation communities, respectively, and "S1 (Housework)", "S9 (Watching TV and/or listening to the radio)", and "D5 (Hopelessness)" were the most prominent bridging nodes between the two communities. Most edges linking the two communities were negative. "S5 (Graden work) - D5 (Hopelessness)" and "S6 (Reading newspapers/books) - D4 (Everything was an effort)" were the top 2 strongest negative edges. Older females had significantly denser network structures than older males. Compared to older people aged 65-80, the age group 81-105 showed higher network global strength. Conclusions: This study provides novel insights into the complex relationships between social participation and depressive symptoms. Except for doing housework, other social participation activities were found to be protective for depression levels. Different nursing strategies should be taken to prevent and alleviate depressive symptoms for different genders and older people of different ages.